Modern analytical supercritical fluid chromatography using columns packed with sub-2 μm particles: a tutorial - Nováková, Lucie; Perrenoud, Alexandre Grand-Guillaume; Francois, Isabelle; West, Caroline; Lesellier, Eric; Guillarme, Davy (Analytica chimica acta, 2014)
This tutorial provides an overview of the possibilities, limitations and analytical conditions of modern analytical supercritical fluid chromatography (SFC) using columns packed with sub-2 μm particles. In particular, it gives a detailed overview of commercially available modern SFC instrumentation and the detectors that can be employed (UV, MS, ELSD, FID, etc.). Some advice on the choice of the stationary phase dimensions and chemistries, the nature of the mobile phase (choice of organic modifier and additives) and its flow rate as well as the backpressure and temperature are also provided. Finally, several groups of potentially problematic compounds, including lipophilic compounds, hydrophilic substances and basic drugs, are discussed in detail. All these families of analytes can be resolved with SFC but require specific analytical conditions.
Keywords: Chromatography, Supercritical Fluid; Mobile phase selection; rozpouštědla; Tutorial; Supercritical fluid chromatography; superkritická fluidní chromatografie; Ultra-high performance supercritical fluid chromatography; velikost částic; Sub-2μm particles; Column selection; Solvents; Particle Size